Pengaruh Penambahan Tepung Tapioka Pada Karakteristik Pelet Kayu dari Limbah Cabang Kayu Jati Perhutani Plus (JPP) - Santiyo Wibowo; Gustan Pari (Fakultas Kehutanan Universitas Gadjah Mada, 2022)
In the cultivation of teak plus Perhutani (JPP) plantations, there is a thinning cycle of plants at a certain age to produce optimal plant growth for other teak trees. The wood waste from thinning in the form of tree tips and branches/twigs is commonly only used as firewood. One of the efforts to diversify the use of thinned JPP wood is processing it into wood pellets. The raw material used is ten years old thinning teak from Perhutani KPH Pemalang, Central Java. The purpose of this study was to identify the effects of adding tapioca flour on the quality of wood pellets from teak branch waste. In this study, the manufacture of pellets was carried out with treatments without the addition of tapioca and the addition of 2.5%, 5%, 7.5%, and 10% w/w of tapioca adhesive. The results showed that the waste of teak branch can be used as raw material for wood pellets, with the characteristics of the water content 6.51-6.97%, volatile matter 76.01-77.37%, ash content 1.37-1.67%, fixed carbon 14.74-15.49%, density 1.14-1.31 g/cm3 and heat value 4192-4319.67 cal/g. The results showed that all parameters met SNI 8021-2014, except for the ash content in the control and 2.5% tapioca treatment.